Experimental evaluation of ZigBee and IEEE 802.15.4 for data-intensive body sensor networks - Gomes, Diogo (2012)
This paper presents results concerning an experimental performance evaluation of ZigBee and IEEE 802.15.4 networks applied to the transport of data-intensive traffic generated by body sensor network applications. The experimental platform is based on the Z-Stack and TIMAC software stacks and the CC2530 device, from Texas Instruments. Three quality of service metrics are evaluated: goodput, delivery ratio and delay. Results are provided for both star and tree topologies. It was observed that the overhead introduced by the stack implementation has a significant impact on the performance results. Overall, the performance of the ZigBee star topology was very good, even in the worst conditions, provided the acknowledgement mechanism was enabled. A router deadlock problem detected in other ZigBee implementations was not observed with the Z-Stack. However, we identified two different situations, triggered by periods of high traffic load, on which the ZigBee router stops relaying packets, causing a significant degradation on the network performance.